Automated mental health screening in pediatric lupus: associations with disease features and treatment - Harper, Lauren; Ardoin, Stacy P.; Leever, Alana; Driest, Kyla; Sivaraman, Vidya; Taxter, Alysha J. (Frontiers in Pediatrics, 2024)
Introduction: Patients with childhood-onset systemic lupus erythematosus (c-SLE) have higher rates of depression than their peers, which has been associated with worse medical outcomes. Therefore, it is imperative that their mental health be addressed. We utilized quality improvement (QI) methodology to automate mental health screening for patients with lupus within a pediatric rheumatology clinic. The retrospective cohort study aims to evaluate the association between mental health screening outcomes and demographics, medications, and disease activity measures in patients with childhood lupus. Methods: The mental health QI team at a quaternary pediatric rheumatology center implemented an automated process for mental health screening in patients with c-SLE. Patients seen between 2017 and June 2023 with a diagnosis of c-SLE were identified using International Classification of Disease -Clinical Modification (ICD-CM) codes. Disease activity was assessed with the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI 2K). Medications were identified on outpatient and inpatient orders for conventional synthetic and biologic disease-modifying antirheumatic drugs, hydroxychloroquine, corticosteroids, and aspirin. Mental health screening was accomplished with the Patient Health Questionnaire (PHQ). Descriptive statistics, univariate and multivariate linear regression were used. Results: Between January 2017 and June 2023, 117 patients with c-SLE (41% with lupus nephritis) completed 534 total screenings. Each patient completed PHQ screenings, a median of 5 [interquartile range 2, 6] times. Screening increased when the screening process was automated. Those who were Black, female, or prescribed leflunomide, mycophenolate, and corticosteroids had higher PHQ scores. Conclusions: Mental health support is essential for patients with chronic rheumatologic diseases such as SLE. Sustainable processes for quickly identifying depression are needed for optimal care of patients with SLE. Our process of automated, streamlined mental health screening successfully increased the screening of patients with SLE at every visit and led to timely interventions for positive PHQ scores. Higher PHQ scores were correlated with patients on leflunomide, mycophenolate, and corticosteroids. Future research should identify modifiable risk factors for high PHQ scores that the medical team can target.